Hippocampal Lesions Impair Retention of Discriminative Responding Based on Energy State Cues. - Davidson, Terry L.; Kanoski, Scott E.; Chan, Kinho (Behavioral Neuroscience, 2010)
The present research investigated the hypothesis that the hippocampus is involved with the control of appetitive behavior by interoceptive “hunger” and “satiety” signals. Rats were trained to solve a food deprivation intensity discrimination problem in which stimuli produced by 0-hr and 24-hr food deprivation served as discriminative cues for the delivery of sucrose pellets. For Group 0+, sucrose pellets were, delivered at the conclusion of each 4-min session that took place under 0-hr food deprivation, whereas no pellets were delivered during sessions that took place when the rats had been food deprived for 24 hr. Group 24+ received the reverse discriminative contingency (i.e., they received sucrose pellets under 24-hr but not under 0-hr food deprivation). When asymptotic discrimination performance was achieved (indexed by greater incidence of food magazine approach behavior on reinforced compared with nonreinforced sessions), half of the rats in each group received hippocampal lesions, and the remaining rats in each group were designated as sham- or nonlesioned controls. Following recovery from surgery, food deprivation discrimination performance was compared for lesioned and control rats in both Groups 0+ and 24+. Discriminative responding was impaired for rats with hippocampal lesions relative to their controls. This impairment was based largely on elevated responding to nonreinforced food deprivation cues. In addition, hippocampal damage was associated with increased body weight under conditions of ad libitum feeding. The results suggest that the inhibition of appetitive behavior by energy state signals may depend, in part, on the hippocampus. Reprinted by permission of the publisher.